Uniqueness and asymptotic behavior of positive solutions for a fractional-order integral boundary-value problem - Xiangbing Zhou; Wenquan Wu (Electronic Journal of Differential Equations, 2013)
In this note, we extend the results by Jia et al [3] to a more general case. By refining the conditions imposed on $f$ and finding more suitable upper and lower solution, we remove some key conditions used in [3], and still establish their results.